Shifting perspectives: can supranationality solve international problems? - Scotton, Damiano; García-Orellana, Diana Alexandra (Frontiers in Political Science, 2025)
This article offers a structural critique of state sovereignty as the foundation of the contemporary international order. Drawing on historical, theoretical, and normative perspectives, it explores the exclusionary origins of the modern state, its limitations in the context of globalization, and the inadequacy of its homogenizing logic in addressing collective identity pluralism. The paper argues that sovereignty has functioned not as a guarantor of peace or recognition, but rather as a mechanism of exclusion and fragmentation. In contrast, it advocates for a shift toward supranational models of governance grounded in universal citizenship, inclusion, and plural representation. By analyzing cases such as the European Union and other regional organizations, the article highlights the potential of pluralist supranationality as a viable and desirable alternative for a more just and sustainable international order. Furthermore, it examines the resurgence of populist and nationalist discourses, especially in the United States, as symptomatic of a deeper structural crisis within the state-centric international system. These developments underscore the urgency of reimagining global governance beyond the constraints of sovereign politics.